The Effects of Cervus nippon on Two Key Ecological Drivers Controlling Populations of Plebejus argus on Heaths: Larval Food Sources and Mutualistic Ants - , S. R. Woodley; , A. Diaz (Archives of Current Research International, 2018)
This study investigated the effects of grazing by invasive sika deer, Cervus nippon on the abundance of the silver-studded blue butterfly Plebejus argus on a lowland heath system in the UK. Plebejus argus is a rare species whose UK stronghold is lowland heath, where it is dependent on a mutalistic relationship with species of Lasius niger ants. Cervus nippon is an invasive species but genetically and ecologically closely related to native red deer C. elaphus and so may have positive as well as negative ecological effects. This study examines the relationship between the incidence of C. nippon and the abundance of P. argus and tests the effect of deer i) directly via their impact on vegetation structure and composition, ii) indirectly their impact on the abundance of L. niger ants. Data were collected from 37 plots of heathland in Dorset, measuring 50 m by 50 m which were differentially grazed by deer. The abundance of P. argus was found to be significantly higher in areas with high incidence of C. nippon and the best predictor of butterfly abundance was the abundance of L. niger ants rather than the abundance of butterfly larval food plants. We conclude that this result provides evidence for an important indirect impact of grazing via manipulating habitat suitability for a key mutualistic species.